PRE-SERVICE EFL TEACHERS’ PERCEPTION TOWARDS FORMATIVE ASSESSMENT IN WRITING SKILL DURING COVID-19 PANDEMIC: THE CASE OF INDONESIA - Depi Rahmawati; Elih Sutisna Yanto; Yousef Bani Ahmad (Universitas Muhammadiyah Tapanuli Selatan, 2021)
Formative assessment in writing aims to monitor students’ progress on an ongoing writing activity. Several studies reports that online formative assessment can improve students’ writing skill and teacher has the main role of the assessment process. In the other hand, as the novice educator, preservice EFL teacher is still lack of knowledge and expertise. Therefore, this study aims to find out the perception of preservice EFL teachers about their own experience in applying online formative assessment for writing skill during teaching practicum program. Three preservice EFL teachers who had experienced in applying online formative assessment for writing skill during COVID-19 pandemic at secondary schools in Indonesia were recruited as the research participants. This study uses narrative case study research design. Online written interview was conducted to collect the data as the information to answer the research question, the interview data then analysed by using thematic analysis. The findings show several perceptions toward online formative assessment for writing skill such as problems in assessing writing skill, tools in online writing formative assessment, and the benefits of formative assessment for writing skill.